Antioxidant-mediated suppression of ferroptosis in Pyricularia oryzae: a novel approach to rice blast management for sustainable rice production - Santoni, Mattia; Molina-Hernandez, Junior Bernardo; Kunova, Andrea; Cortesi, Paolo; Brunetti, Barbara; Rocculi, Pietro; Christodoulou, Michael S.; Danesi, Francesca (Frontiers in Plant Science, 2024)
Ferroptosis, an iron-dependent form of regulated cell death, has recently emerged as a crucial process in the pathogenesis of Pyricularia oryzae, the causal agent of the devastating rice blast disease, which causes billions of dollars in annual losses. This mini review explores the potential of antioxidants in suppressing ferroptosis in P. oryzae to promote sustainable rice production, with significant implications for global food security and nutrition. We critically analyze the current literature on the mechanisms of ferroptosis in P. oryzae, including iron metabolism and lipid peroxidation, the role of different antioxidants in inhibiting this cell death pathway, and the potential applications of antioxidant-based strategies for the management of rice blast disease. Recent discoveries, such as the efficacy of the natural flavonoid tangeretin in inhibiting fungal ferroptosis by interfering with the accumulation of iron and reactive oxygen species, highlight the promise of natural and nature-inspired compounds for disease management. The use of antioxidants to modulate ferroptosis in P. oryzae offers several advantages over traditional fungicide-based approaches, including improved safety, sustainability, and potential nutritional benefits through antioxidant-enriched rice varieties. However, challenges such as optimizing delivery methods, managing potential resistance, and ensuring efficacy under different environmental conditions need to be addressed. To achieve these goals, future research should focus on identifying the most effective antioxidant compounds, exploring synergistic combinations, and developing sustainable application methods.